Merit and Propassions in the De Tristitia Christi: A Genealogical Account1. (June 2016) - Bielinski, Maureen
Abstract : This paper aims to uncover the groundwork in philosophy and moral theology for Thomas More's claim in the De Tristitia Christi that Christ's death was more meritorious because he overcame conflicting passions during his agony. It argues that this claim relies on the treatments of Christ's dual nature, the passions, and moral virtue that Thomas Aquinas lays out in the Summa Theologiae . In particular, given Aquinas's distinction between passions and propassions, Aquinas's explanation of the conflict between the natural ordering of the sense appetite away from pain, and the rational ordering of the will toward the highest goal, can offer a defense of More's conclusion. It accounts for the uninhibited rule of reason in the soul of the perfectus homo, as well as the opportunity presented by contrary propassions to increase virtue and merit. Further, since Erasmus adopts Aquinas's position in the Disputatiuncula de taedio, this paper seeks to show how Erasmus served as an intermediate source of Thomistic thought for More. It concludes by pointing out some ways in which More develops and applies Aquinas's work to the lives of fearful martyrs and of ordinary Christians.